Blinatumomab for Acute Lymphoblastic Leukemia: The First Bispecific T‐Cell Engager Antibody to Be Approved by the EMA for Minimal Residual Disease. (14th November 2019) - Ali, Sahra; Moreau, Alexandre; Melchiorri, Daniela; Camarero, Jorge; Josephson, Filip; Olimpier, Odoardo; Bergh, Jonas; Karres, Dominik; Tzogani, Kyriaki; Gisselbrecht, Christian; Pignatti, Francesco
Abstract: : On November 15, 2018, the Committee for Medicinal Products for Human Use (CHMP) recommended the extension of indication for blinatumomab to include the treatment of adults with minimal residual disease (MRD) positive B‐cell precursor acute lymphoblastic leukemia (ALL). Blinatumomab was authorized to treat relapsed or refractory B‐precursor ALL, and the change concerned an extension of use. On March 29, 2018, the U.S. Food and Drug Administration (FDA) granted accelerated approval to blinatumomab to treat both adults and children with B‐cell precursor ALL who are in remission but still have MRD. On July 26, 2018, the CHMP had originally adopted a negative opinion on the extension. The reason for the initial refusal was that although blinatumomab helped to reduce the amount of residual cancer cells in many patients, there was no strong evidence that it led to improved survival. During the re‐examination, the CHMP consulted the scientific advisory group. The CHMP agreed with the expert group's conclusion that, although there was no strong evidence of patients living longer, the available data from the main study (MT103‐203) indicated a good durable response to blinatumomab, with an overall complete response rate for the primary endpoint full analysis set (defined as all subjects with an Ig or T‐cell receptor polymerase chain reaction MRD assay with the minimum required sensitivity of 1 × 10 –4 at central lab established at baseline [ n = 113]) as 79.6% (90/113; 95% confidence interval, 71.0–86.6), with a median time to complete MRD response of 29.0 days (range, 5–71). Therefore, the CHMP concluded that the benefits of blinatumomab outweigh its risks and recommended granting the change to the marketing authorization. The Committee for Orphan Medicinal Products, following reassessment, considered that significant benefit continued to be met and recommended maintaining the orphan designation and thus 10 years market exclusivity (the Orphan Designation is a legal procedure that allows for the designation of a medicinal substance with therapeutic potential for a rare disease, before its first administration in humans or during its clinical development). The marketing authorization holder for this medicinal product is Amgen Europe B.V. Abstract : This article summarizes the European Public Assessment Report by the Committee for Medicinal Products for Human Use that recommended the extension of indication for bliatumomab to include the treatment of adults with minimal residual disease positive B cell precursor acute lymphoblastic leukemia.